Analysis of Selected Seismic Events from Asia in a Seismic Discrimination Context - Sobel, P A; von Seggern, D H (1978)
This study examines earthquakes in Kamchatka, the Tien Shan, the Pamirs, the Baikal rift zone, and the Caucasus and explosions in the Aleutians, East Kazakh, West Kazakh, Southwest Russia, Lop Nor, and Baikal in a seismic discrimination context. Because of their low magnitudes (m sub b from 4.2 to 6.0 and M sub s from 3.2 to 5.8) and their varying propagation effects, it was impossible on the basis of first motions or LR amplitudes to determine source mechanisms for most of the earthquakes. Seismograms from the arrays ALPA, LASA, and NORSAR, the HGLP and the WWSSN stations were analyzed for m sub b, M sub s, corner frequency, long-period spectral level, long-period and short-period body- wave excitation, complexities, spectral ratios, radiation patterns, depth of focus, and higher-mode surface waves. The major successful discriminants for our data set were found to be M sub s-m sub b and identification of pP. In a stepwise linear discrimination analysis using the discrimination parameters M sub b, M sub s, corner frequency, complexity, spectral ratio, and long-period spectral level, the earthquakes were separated from the explosions with high confidence. In addition, some separation by region was evident for the earthquakes alone.